2009
DOI: 10.1016/j.jvoice.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Child Voice and Noise: A Pilot Study of Noise in Day Cares and the Effects on 10 Children's Voice Quality According to Perceptual Evaluation

Abstract: SummaryThe purpose of this investigation was to study children's exposure to background noise at the ears during a normal day at the day care center and also to relate this to a perceptual evaluation of voice quality. Ten children, from three day care centers, with no history of hearing and speech problems or frequent infections were selected as subjects. A binaural recording technique was used with two microphones placed on both sides of the subject's head, at equal distance from the mouth. A portable digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 27 publications
1
54
3
2
Order By: Relevance
“…1,19 Laryngeal assessment was not performed due to the professionals' diffi culty in leaving the classroom. Roughness, breathiness and hyperfunction/strain have been prevalent in other studies, 13,19 but only one 19 found alterations related to phonotrauma by means of laryngeal assessment.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…1,19 Laryngeal assessment was not performed due to the professionals' diffi culty in leaving the classroom. Roughness, breathiness and hyperfunction/strain have been prevalent in other studies, 13,19 but only one 19 found alterations related to phonotrauma by means of laryngeal assessment.…”
Section: Resultsmentioning
confidence: 76%
“…3,4,9,10,15,16,23,24 Another study has found an association between high noise levels and vocal alteration in teachers of one out of three analyzed schools. 13 The adhesion of all the invited educators shows interest and need of research in the voice area in this professional category. The lack of studies on the theme points to the need of research that aims at environmental characterization and the problems it may cause to professionals and students, and also at evaluating multidisciplinary actions of health promotion in the search of a better quality of life to those who are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The children had no history of hearing or speech problems, or frequent ear, nose, and throat infections. No initial survey of voice quality was made.…”
Section: Subjectsmentioning
confidence: 99%
“…In the evaluation protocol, all parameters were represented by a 100-mm visual analog scale (VAS) with ''not at all'' and ''a lot'' at the extremes, except for the parameter pitch, represented by a 200-mm line with ''very high'' and ''very low'' at the extremes. 18 The other parameters were hoarseness, breathiness, roughness, hyperfunction, and an open parameter to offer options for the raters, if necessary. Three repetitions of each set of sentences for each condition, controlled sentences or sentences selected from spontaneous speech were presented to the listener on a computer using Sennheiser PX200 headphones.…”
Section: Perceptual Evaluationmentioning
confidence: 99%